Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+y\right)^2-2xy=x^2+y^2=4^2-2.1=14\)
\(x^4+y^4=\left(x^2+y^2\right)^2-2x^2y^2=14^2-2=196-2=194\)
\(x^3+y^3=\left(x+y\right)\left(x^2+y^2-xy\right)=4\left(14-1\right)=52\)
\(\left(x^4+y^4\right)\left(x+y\right)=194.4=776\Leftrightarrow x^5+y^5+x^4y+y^4x=\left(x^5+y^5\right)+xy\left(x^3+y^3\right)=\left(x^5+y^5\right)+1.52=\left(x^5+y^5\right)+52=776\Rightarrow x^5+y^5=724\)
\(\left\{{}\begin{matrix}x+y=4\\xy=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x^2+2xy+y^2=16\\4xy=4\end{matrix}\right.\Rightarrow x^2+2xy-4xy+y^2=\left(x-y\right)^2=12mà:x>y\Leftrightarrow x-y>0\Rightarrow x-y=\sqrt{12}=2\sqrt{3};x+y=2.2\Rightarrow\left\{{}\begin{matrix}x=\sqrt{3}+2\\y=2-\sqrt{3}\end{matrix}\right.\)
\(x^2-y^2=\left(x-y\right)\left(x+y\right)=4.2\sqrt{3}=8\sqrt{3}\)
\(\left(x^2+y^2\right)\left(x^2-y^2\right)=8\sqrt{3}.14=112\sqrt{3}\Rightarrow x^4-y^4=112\sqrt{3}\)
\(\left(x^3-y^3\right)=\left(x-y\right)\left(x^2+xy+y^2\right);x^6-y^6=\left(x^3+y^3\right)\left(x^3-y^3\right)tựlm\)
ĐK: !x! khác !y!
\(B=\frac{x^2}{\left(x-y\right)^2\left(x+y\right)}-\frac{2xy^2}{\left(x-y\right)^2\left(x+y\right)^2}+\frac{y^2}{\left(x-y\right)\left(x+y\right)^2}\) =>\(MSC=\left(x-y\right)^2\left(x+y\right)^2\)
\(B=\frac{x^2\left(x+y\right)-2xy^2+y^2\left(x-y\right)}{MSC}=\frac{x^3+x^2y-2xy^2+y^2x-y^3}{MSC}=\frac{x^3+x^2y-xy^2-y^3}{MSC}\)
\(B=\frac{x^3+x^2y-xy^2-y^3}{MSC}=\frac{x^2\left(x+y\right)-y^2\left(x+y\right)}{MSC}=\frac{\left(x+y\right)^2\left(x-y\right)}{\left(x-y\right)^2\left(x+y\right)^2}=\frac{1}{x-y}\)
c: \(=\dfrac{1}{3x-2}-\dfrac{4}{3x+2}+\dfrac{3x-6}{\left(3x-2\right)\left(3x+2\right)}\)
\(=\dfrac{3x+2-12x+8+3x-6}{\left(3x-2\right)\left(3x+2\right)}\)
\(=\dfrac{-6x+4}{\left(3x-2\right)\left(3x+2\right)}=\dfrac{-2}{3x+2}\)
d: \(=\dfrac{x^2-4-x^2+10}{x+2}=\dfrac{6}{x+2}\)
e: \(=\dfrac{1}{2\left(x-y\right)}-\dfrac{1}{2\left(x+y\right)}-\dfrac{y}{\left(x-y\right)\left(x+y\right)}\)
\(=\dfrac{x+y-x+y-2y}{2\left(x-y\right)\left(x+y\right)}=0\)
\(P=\left(x-y\right)^2+\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)-4x^2=\left(x-y-x-y\right)^2-\left(2x\right)^2=\left(-2y\right)^2-\left(2x\right)^2\)
\(=\left(2y-2x\right)\left(2y+2x\right)=2\left(y-x\right)2\left(y+x\right)=4\left(x+y\right)\left(y-x\right)\)
\(x^3-x^2y+3x-3y=x^2\left(x-y\right)+3\left(x-y\right)=\left(x-y\right)\left(x^2+3\right)\)
\(x^3-2x^2-4xy^2+x=x\left(x^2-2x+1-4y^2\right)=x\left[\left(x-1\right)^2-\left(2y\right)^2\right]=x\left(x+2y-1\right)\left(x-2y-1\right)\)
\(\left(x+2\right)\left(x+3\right)\left(x+4\right)\left(x+5\right)-8=\left(x^2+7x+10\right)\left(x^2+7x+12\right)-8\)
Đặt \(x^2+7x+10=t\), ta có:
\(t\left(t+2\right)-8=t^2+2t-8=t^2-2t+4t-8=t\left(t-2\right)+4\left(t-2\right)=\left(t-2\right)\left(t+4\right)\)
\(=\left(x^2+7x+10+4\right)\left(x^2+7x+10-2\right)=\left(x^2+7x+14\right)\left(x^2+7x-8\right)\)